2018
DOI: 10.1042/bst20170149
|View full text |Cite
|
Sign up to set email alerts
|

Nesprin-1/2: roles in nuclear envelope organisation, myogenesis and muscle disease

Abstract: Nesprins (nuclear envelope spectrin repeat proteins) are multi-isomeric scaffolding proteins. Nesprin-1 and -2 are highly expressed in skeletal and cardiac muscles and together with SUN (Sad1p/UNC84) domain-containing proteins form the LInker of Nucleoskeleton and Cytoskeleton (LINC) complex at the nuclear envelope in association with lamin A/C and emerin. Mutations in nesprin-1/2 have been found in patients with autosomal dominant Emery-Dreifuss muscular dystrophy (EDMD) as well as dilated cardiomyopathy (DCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 84 publications
2
62
0
Order By: Relevance
“…We now show that nesprin-1 is present on the nuclear envelope in hippocampal neurons (Fig. 1B), just as we have previously shown for mAKAP␣ (Michel et al, 2005) and as found for nesprin-1 in other neurons and other cell types (Gros-Louis et al, 2007;Zhou et al, 2018). Expression of a GFP-tagged fragment encoding the mAKAP spectrin-repeat domains (amino acid residues 586 -1286, "mAKAP-SR-GFP"; Fig.…”
Section: Makap␣ Anchoring By Nesprin-1␣ Is Required For Neurite Extensupporting
confidence: 86%
See 2 more Smart Citations
“…We now show that nesprin-1 is present on the nuclear envelope in hippocampal neurons (Fig. 1B), just as we have previously shown for mAKAP␣ (Michel et al, 2005) and as found for nesprin-1 in other neurons and other cell types (Gros-Louis et al, 2007;Zhou et al, 2018). Expression of a GFP-tagged fragment encoding the mAKAP spectrin-repeat domains (amino acid residues 586 -1286, "mAKAP-SR-GFP"; Fig.…”
Section: Makap␣ Anchoring By Nesprin-1␣ Is Required For Neurite Extensupporting
confidence: 86%
“…For live cell imaging, Cos-7 cells were plated onto 25-mm-diameter sterilized glass coverslips in 6-well plates and were either transfected with polyethylenimine or infected with adenovirus at 60 -70% confluence and allowed to grow for 24 -48 h before live cell imaging. Nesprin-1␣ fusion proteins are not properly localized to the nuclear envelope when grossly overexpressed due to saturation of Klarsicht/ANC-1/Syne-1 homology (KASH)-SUN domain protein-protein interactions (Zhou et al, 2018). Only Cos-7 cells and neurons with epifluorescence for PN-AKAR and the other nesprin-1␣ fusion proteins restricted to the nuclear envelope were included in the studies.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…and SYNE-1/2 both encode Nesprin proteins that perform many similar functions, including regulation of glutamate receptor expression (Cottrell et al, 2004;Morel et al, 2014) and positioning of myonuclei (Stroud et al, 2017;Volk, 2013;Wang et al, 2015;Zhou et al, 2018a). The functional role of Nesprins in the nervous system is more enigmatic and requires further attention because mutations in SYNE-1 and -2 are strongly linked to recessive forms of hereditary cerebellar and extra-cerebellar ataxias in humans Gros-Louis et al, 2007;Noreau et al, 2013;Synofzik et al, 2016;Wiethoff et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The Nesprins are encoded by synaptic nuclear envelope-1 and -2 (SYNE-1 and -2), which contain at least 80 disease-related variants that cause cerebellar ataxias or muscular dystrophies (Zhou et al, 2018b). The molecular function of Nesprins and their role in muscular diseases are relatively well studied in mouse models of SYNE-1 and SYNE-2 (Zhou et al, 2018a) in relation to nucleo-cytoplasmic and cytoskeletal organization and function, but the function of Nesprins in neurological disorders…”
Section: Introductionmentioning
confidence: 99%